Gogol's crime and punishment: an essay in the interpretation of Nikolai Gogol's dead souls - Heftrich, Urs (Studies in Russian and slavic literatures, cultures, and history, 2022)
Frontmatter -- Brief Contents -- Detailed Contents -- Acknowledgments -- Foreword -- Introduction: Of Beauty, Truth, and Evil -- Part One: Chichikov's Prehistory -- 1. Ethos and Epic -- 2. The Ground Plan of Dead Souls -- 3. The Ground Plan of Dead Souls Revisited -- Part Two: Chichikov's Crime -- 4. On Truth and Lies in a Moral Sense -- 5. The Five Faces of Lying -- 6. In the Shadow Realm of Lies -- Part Three: Chichikov's Punishment -- 7. Judgment and Rumor -- 8. The Five Acts of the Drama -- 9. Ethos and Epic: Chichikov's Crime and Punishment -- List of Sources for Illustrations -- Bibliography -- Index